Mitford, Madame De Pompadour - Musselwhite, Laura (Teaching History: A Journal of Methods, 2002)
Madame de Pompadour by Nancy Mitford is as much a cultural icon as a work of history. Mitford, a British aristocrat born in 1904, was known for writing historical biographies as well as several novels, such as The Pursuit of Love ( 1945) and Don't Tell Alfred (1960). This particular text is a reprint of the 1953 original with an introduction by Amanda Foreman, author of the recent Georgiana, Duchess of Devonshire. Foreman attempted to resuscitate Mitford's reputation by emphasizing her love of learning, her vulnerability, and the popular success of her books. Denied an education by their father, Mitford and her sisters gathered whatever information they could from the family library.